The Plagiarism Allegation in English Literature from Butler to Sterne - Terry, R. author. aut Link
VIII, 215 p.
Keywords: Contributing to the growth in plagiarism studies, this timely new book highlights the impact of the allegation of plagiarism on the working lives of some of the major writers of the period, and considers plagiarism in relation to the emergence of literary copyright and the aesthetic of originality.